Multidisciplinary management of a norovirus outbreak in Tuscany, Italy - Clara Girardi; Lucia Kundisova; Francesca Marconi; Alessandra Guidi; Johanna Alexandra Iamarino; Veronica Gallinoro; Silvia Mele; Giovanni Nardone; Maurizio Grani; Giovanni Munaò; Luca Cianti; Paola Picciolli; et al. (Italian Journal of Food Safety)
Norovirus (NoV) is one of the most frequent agents responsible for foodborne outbreaks. Transmission occurs through the consumption of contaminated food or water or via contact with contaminated surfaces. The low infectious dose and high environmental resistance of the virus facilitate its spread within communities and healthcare settings, complicating epidemiological investigations. This study aims to highlight the management strategies and key entities involved in outbreak response, emphasizing the importance of coordinated efforts to share best practices. The outbreak occurred in Tuscany in April 2024 and affected multiple school groups. The response team was activated in accordance with guidelines for managing foodborne diseases and comprised various public health authorities. The team undertook a series of coordinated actions, including epidemiological investigation, official controls, sampling, and analysis of relevant matrices to identify high-risk foods. Food and water samples collected during the official inspection at the accommodation facility involved in the outbreak during the first wave were tested for potential pathogenic bacteria. Additionally, fecal samples from ten hospitalized cases were analyzed for pathogenic bacteria and viruses. Among all these analyses, only the fecal samples from the examined cases tested positive for NoV genogroups GI and GII. In light of these results, during the second wave, food and water were tested again for the same potential pathogenic bacteria and for the presence of NoV. Furthermore, NoV was investigated in staff fecal samples and environmental surfaces. A total of four fecal samples from staff and two environmental swabs tested positive for NoV genogroups GI and GII. Our multidisciplinary investigation suggests that an initial foodborne transmission may have led to environmental contamination. This finding underscores the critical role of food safety culture in outbreak prevention and control. To reduce the risk of viral gastroenteritis, specific awareness initiatives and training programs should be offered to both food sector operators and the general public.